2018
DOI: 10.1097/ijg.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Features in an East African Population: A 6-Year Cohort Study of Older Adults in Nakuru, Kenya

Abstract: Glaucoma is a public health challenge in low-resource settings. Research into testing and treatment modalities in Africa is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…However, surveys have routinely shown that cataract is the condition most associated with blindness or visual impairment in sub-Saharan Africa. 4 Previous studies of the overall incidence of blindness and visual impairment, 5 macular degeneration, 6 diabetes and diabetic retinopathy, 7 and glaucoma 8 used data from the Nakuru Eye Disease Cohort Study. This cohort study of adults aged 50 years or older living in Nakuru, a city in the Rift Valley region in Kenya, was deemed to be a regionally and nationally representative sample that could inform the eye care needs and priorities of the entire country.…”
Section: Introductionmentioning
confidence: 99%
“…However, surveys have routinely shown that cataract is the condition most associated with blindness or visual impairment in sub-Saharan Africa. 4 Previous studies of the overall incidence of blindness and visual impairment, 5 macular degeneration, 6 diabetes and diabetic retinopathy, 7 and glaucoma 8 used data from the Nakuru Eye Disease Cohort Study. This cohort study of adults aged 50 years or older living in Nakuru, a city in the Rift Valley region in Kenya, was deemed to be a regionally and nationally representative sample that could inform the eye care needs and priorities of the entire country.…”
Section: Introductionmentioning
confidence: 99%
“…This subset of our participants had about the same CECD as Nepali, Bangladeshi and Indians who were undergoing cataract surgery in South Asia [8]. Although CCT (504.2 μm) of those 50 years and older in the present study (n = 82) mirrored that of participants in the Nakuru Eye Disease Cohort Study [49], it was thinner than found in the Yunnan Minority Eye Studies [7], the Reykjavik Eye Study [50], and the Rotterdam Study [51]. This pattern is similar to what we observed after comparison with subjects of African and those of European heritage drawn from the African Descent and Glaucoma Evaluation Study (ADAGES) [22], participants of the Gutenberg Health Study [25], as well as other studies [17,46].…”
Section: Discussionmentioning
confidence: 69%
“…Also, with similar findings, the city of Tema (Ghana) had a prevalence of glaucoma of 6.5% (95% CI 5.8–7.1), POAG of 6.1% (no CI available) and PACG of 0.2% (no CI available) 17 . In people older than 50 years, Nakuru district (Kenya) had a prevalence of glaucoma of 4.3% (95% CI 3.5–5.9) 20 …”
Section: Africamentioning
confidence: 99%
“…17 In people older than 50 years, Nakuru district (Kenya) had a prevalence of glaucoma of 4.3% (95% CI 3.5-5.9). 20…”
Section: Africamentioning
confidence: 99%